Kenya : First Reviews of the Extended Arrangement Under the Extended Fund Facility and an Arrangement Under the Extended Credit Facility and Requests for Modifications of Performance Criteria and Structural Conditionality-Press Release; Staff Report; and Statement by the Executive Director for Kenya. (IMF Staff Country Reports; Country Report ;, 2021)
Kenya was hit by a third COVID-19 wave in March and April 2021, with renewed containment measures eased in May as the case count moderated. In mid-May, Kenya's COVID-19 vaccination program faced serious challenges on delays in international vaccine shipments. The authorities are redoubling their efforts to mobilize support and now aim to inoculate 60 percent of the population by mid-2023. General elections are planned for August 2022.